APPLICATION OF TEACHING METHODS FOR STUDENTS IN KINDERGARTEN USING SWISH 2.0 AT LITTLE BEAR - Mahyudin Dehi; Fitri Syafrina, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Kindergarten is one form of pre-school education that provides educational programs for children aged four years which aims to help lay the basic attitude towards the development of knowledge, skills and creativity that are needed by children to adjust to the surrounding. Kindergarten litle bear is one of the schools in teaching and learning process is still using props that take a long time in creating these props. Swish 2.0 application program is one alternative to solve the problems above. This program requires Windows-based computers. With this swish made program can assist in developing the power of thought and creativity of children and help teachers in teaching.